ANALISIS PENGARUH ROA, SALES, HARGA SAHAM, BOARD OF COMMISSIONERS DAN BOARD INDEPENDENCE TERHADAP PERGANTIAN CEO DI INDONESIA (Studi Empiris : Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia periode 2009 sampai dengan 2013) - Triwidayanti, Nurulita; Indriani, Astiwi (Faculty of Economics and Business Diponegoro University, 2015)
This Research aimed to analyze the influence of Return On Assets (ROA), sales, stocks price, board of commissioners, and board independence towardCEO turnover in Indonesia. Case Study on manufacture corporates in Indonesia Stock Exchange in period 2009-2013.Research population used was manufacture corporates in Indonesia Stock Exchange in period 2009-2013. The method used was purposive sampling method with the result that it was obtained a sample of 87 companies The data used in this research were obtained from the Annual Report 2009-2013 and Indonesia Capital Market Directory (ICMD) 2008- 2014. Analysis technique used was statistical t-test, Logistic Regression that includes hosmer and lemeshow’s goodness of fit test, overall model fit, nagelkerke R square and hypothesis test.The result showed that Return On Asset had significant negative association with CEO Turnover, sales had insignificant negative association with CEO Turnover, and stocks price had significant positive association with CEO Turnover. Board of commissioners had significant positive association with CEO Turnover, and board independence had insignificant negative association with CEO Turnover. The results of regression estimation showed the ability of model prediction was 6,8% while the remaining 93,2% influenced by other factors outside the model.